2014
DOI: 10.4055/cios.2014.6.3.267
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Pronator Quadratus Muscle during Hardware Removal Procedures after Volar Plating for Distal Radius Fractures

Abstract: BackgroundIt is not clear whether the pronator quadratus (PQ) muscle actually heals and provides a meaningful pronation force after volar plating for distal radius fractures (DRFs). We aimed to determine whether the length of the PQ muscle, which is dissected and then repaired during volar plating for a DRF, affects the forearm rotation strength and clinical outcomes.MethodsWe examined 41 patients who requested hardware removal after volar plating. We measured the isokinetic forearm rotation strength and clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Since we have excluded patients with anterior rotatory muscle injury before the study, we do not believe that primary injury is a common cause of postoperative loss of muscle function. Nho [15] also confirmed that the PQ muscle was atrophic during the removal of internal fixation, and that the muscle width was independent of the final clinical functional outcome, suggesting that the PQ muscle may be functionally lost after suture. Because pronator teres is the main muscle of forearm pronation [17], the loss of pronator teres can be compensated by pronator teres, so that forearm rotation can be preserved.…”
Section: Discussionmentioning
confidence: 67%
“…Since we have excluded patients with anterior rotatory muscle injury before the study, we do not believe that primary injury is a common cause of postoperative loss of muscle function. Nho [15] also confirmed that the PQ muscle was atrophic during the removal of internal fixation, and that the muscle width was independent of the final clinical functional outcome, suggesting that the PQ muscle may be functionally lost after suture. Because pronator teres is the main muscle of forearm pronation [17], the loss of pronator teres can be compensated by pronator teres, so that forearm rotation can be preserved.…”
Section: Discussionmentioning
confidence: 67%
“…Nanno et al observed that the transverse gliding area of the FPL at the volar distal radius rim could be covered by the PQ suture to protect the FPL from attrition on the plate. Then, suturing the PQ may act as a protective sleeve to protect the flexor tendons on the distal part of the plate, even if the suture is partial or loose . This suture is considered difficult because of a thin muscle, which is often torn by the fracture.…”
Section: Discussionmentioning
confidence: 99%
“…For example, electromyographical (EMG) analysis of muscle activation patterns upon DRUJ loading and increased knowledge on the necessity of the deep head of PQ as a primary stabilizer for the DRUJ. 13,14 Despite this, it still remains unclear whether or not repairing of the PQ after volar plating of DRFs has any positive effect on clinical outcome. 11,14,15 This is a functionally important question that we hope to be able to address with the torque meter eventually.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Despite this, it still remains unclear whether or not repairing of the PQ after volar plating of DRFs has any positive effect on clinical outcome. 11,14,15 This is a functionally important question that we hope to be able to address with the torque meter eventually. Also, effects of isometric and isotonic muscular activation on stability can be addressed to further strengthen the current proposed test design.…”
Section: Discussionmentioning
confidence: 99%